1983
DOI: 10.1007/bf01976350
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Rhizoctonia solani on potatoes by antagonists. 1. Preliminary experiments with Verticillium biguttatum, a sclerotium-inhabiting fungus

Abstract: Abstrac!A common mycoparasite, Verticillium biguttatum, was found to kill sclerotia of Rhizoctonia solani placed on an inert material (perlite) as well as in soil at 15 ~ and 20 ~ but not at 10 ~ Compared with the effectivity of V. biguttatum, that of Gliocladium roseum, Gliocladium nigrovirens, Hormiactis fimicola and Trichoderma h'amatum on sclerotia was only low. In laboratory experiments, treatment of scler0tia-bearing seed potatoes with V. biguttatum reduced disease symptoms in the first stage of growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The isolates varied widely in antagonistic activity. One isolate, M73, was outstanding; when it had been inoculated on germinating seed tubers it was found to be present on the surface of the sprouts up to the soil surface and gave protection to the sprouts against infection by R. solani from sclerotia on the seed tuber (Velvis and Jager, 1983) and from soilborne R. solani (Jager and Velvis, 1984). These properties would make V. biguttatum very suitable for biological control of R. solani in potato fields.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The isolates varied widely in antagonistic activity. One isolate, M73, was outstanding; when it had been inoculated on germinating seed tubers it was found to be present on the surface of the sprouts up to the soil surface and gave protection to the sprouts against infection by R. solani from sclerotia on the seed tuber (Velvis and Jager, 1983) and from soilborne R. solani (Jager and Velvis, 1984). These properties would make V. biguttatum very suitable for biological control of R. solani in potato fields.…”
Section: Introductionmentioning
confidence: 96%
“…Velvis and Jager (1983) observed that certain isolates of E biguttatum could kill sclerotia within seven weeks under high relative humidity and at a temperature of 15 ~ or higher. The isolates varied widely in antagonistic activity.…”
Section: Introductionmentioning
confidence: 98%
“…omnivorum: soil plate method (SPM) (Arora and Dwivedi 1979;Dos Santos and Dhingra 1982;Henis et a1 . 1984;Makkonan and Pohjakallio 1960;Mueller et al 1985;Velvis and Jager 1983;Zazzerini and Tosi 1985), soil immersion method (SIM), and inert carrier method (ICM) (Fig. 1).…”
Section: Methodsmentioning
confidence: 98%
“…solani was assessed according to a modification by Velvis [1977] of the method of Sneh and Henis [1972], by measuring the colony diameter after three days growth at 20 ~ on Whatman no. 1 filter paper on wet soil.…”
Section: Determination Of Rhizoctonia-inhibiting Factors Thementioning
confidence: 99%